The double burden of malnutrition and dietary patterns in rural Central Java, Indonesia - Callum Lowe; Mattthew Kelly; Haribondhu Sarma; Alice Richardson; Johanna M. Kurscheid; Budi Laksono; Salvador Amaral; Donald Stewart; Darren J. Gray (The Lancet Regional Health. Western Pacific, 2021)
Background: Indonesia is undergoing a nutrition transition (NT) comprised of rising rates of overweight/obesity and consumption of high fat food/snacks but is still struck by undernutrition, causing a double burden of malnutrition. Little research pertains to the double burden of malnutrition and its associations with diet in rural Indonesia using primary village level data. Methods: We conducted a 24-hour food recall and food frequency questionnaire and assessed anthropometric status of rural villagers from four villages in Central Java, Indonesia. Exploratory principal component analysis was used to identify dietary patterns and multi-level modeling was performed to identify variables associated with dietary pattern indicative of the NT. Findings: 1,521 participants were included in analysis. Double burden of malnutrition was prevalent whereby 32.3% of children were stunted, 68.8% of women 35–49 years-old were overweight, and 39% of homes were classified as double burden. The NT was evident in a dietary pattern associated with soft drink, snacks, and animal products. There was small but significant correlation between undernutrition and stunting status among children (r = −0.139, p < 0.01). The NT was associated with young age (B = 1.696, 95% CI = 1.508–1.885) but not with overweight (B = −0.099, 95% CI = −0.184–−0.013). Interpretation: Our findings suggest that whilst the typical pattern of the double burden of malnutrition (stunted child/overweight adult) exists in rural Central Java, dietary patterns indicative of the NT are predominant among children, not adults. Overweight among adults may not be necessarily due to a diet indicative of the NT, and nutrition interventions in rural Central Java should focus on educating parents of young children about the health-risks of a diet associated with a NT. Funding: Funding was obtained from the UBS-Optimus Foundation and the National Health and Medical Research Council.